Calcined coke, preparation method thereof and carbon anode for aluminum
By mixing biomass carbon and organic gel materials with dust collecting powder and molding and calcining, the problem that dust collecting powder cannot enter the production process of carbon anode for aluminum is solved, and efficient utilization of dust collecting powder and excellent performance of calcined coke are achieved.
Patent Information
- Application Number
- CN202411811718.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
In the production of carbon anode for aluminum, petroleum coke calcined dust collecting powder cannot enter the mainstream production process due to its small particle size and poor adhesion, resulting in increased production costs and environmental pollution.
By mixing biomass carbon and organic gel material with dust collecting powder, a composite binder is formed, and the dust collecting powder particle size is increased to 1 mm to 100 mm through molding treatment, and finally calcined treatment is carried out to prepare a calcined coke that meets the production requirements of carbon anode for aluminum.
The efficient utilization of dust collecting powder is achieved, and the calcined coke with excellent performance can be prepared, which can be directly used for the production of carbon anode for aluminum, reducing production costs and avoiding environmental pollution.
Smart Images

Figure CN119614225A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon anodes for aluminum, and in particular to a calcined coke and a preparation method thereof, and a carbon anode for aluminum. Background Art
[0002] Calcined coke is one of the main raw materials for aluminum carbon anodes. It is generally obtained by calcining petroleum coke. About 41 million tons of petroleum coke are calcined to obtain calcined coke every year in the world, of which 75% are used for the production of aluminum carbon anodes. Petroleum coke calcined dust powder refers to the powder collected by the dust collector during the calcination heat treatment process. The equipment currently used for calcining petroleum coke in my country's aluminum industry mainly includes two types: tank furnace and rotary kiln. The amount of calcined dust powder collected every year is huge. These dust powders affect the formula balance and stability of the production process, resulting in fluctuations in the volume density, strength, resistivity and other indicators of the carbon anode, and cannot enter the main production process of aluminum carbon anodes. The main treatment method is to sell them at a low price. This not only leads to an increase in the production cost of carbon enterprises, but also the dust powder is very easy to leak during the transportation and takeaway process of the enterprise, causing secondary pollution to the environment. Summary of the invention
[0003] The present application provides a calcined coke and a preparation method thereof and a carbon anode for aluminum to solve the following technical problem: how to achieve efficient utilization of dust collected in the carbon industry.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing calcined coke, the method comprising:
[0005] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0006] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0007] Molding the mixed material to increase the particle size of the dust collecting powder to 1 mm to 100 mm, thereby obtaining molded particles with strength;
[0008] The shaped particles are calcined to obtain calcined coke.
[0009] Optionally, the mass ratio of the biomass carbon to the organic gel material is (0.01-3):1; and / or,
[0010] The mass ratio of the mixture of the biomass carbon and the organic gel material to the first dispersant is 1:(0.01-5).
[0011] Optionally, the biomass carbon includes at least one of the following: starch, sucrose, cellulose; and / or,
[0012] The organic gel material includes at least one of the following: coal tar, petroleum asphalt, and phenolic resin.
[0013] Optionally, the mass ratio of the composite binder to the dust collecting powder is (0.01-1):1; and / or,
[0014] The mass ratio of the mixture of the composite binder and the dust collecting powder to the second dispersant is 1:(0.01-5).
[0015] Optionally, the molding pressure is 1Mpa to 50Mpa.
[0016] Optionally, the molded particles meet the following indicators: particle size is 1 mm to 100 mm, and drop strength is ≥10%.
[0017] Optionally, the calcination temperature is 700°C to 1450°C.
[0018] Optionally, the calcined coke meets the following indicators: particle stability is ≥30%, resistivity is ≤550 μΩ·m, and ash content is <1%.
[0019] In a second aspect, an embodiment of the present application provides a calcined coke, which is prepared by the method described in any embodiment of the first aspect.
[0020] In a third aspect, an embodiment of the present application provides a carbon anode for aluminum, wherein the raw material of the carbon anode for aluminum includes the calcined coke described in any one embodiment of the second aspect.
[0021] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0022] The preparation method of the calcined coke provided in the embodiment of the present application comprises: mixing biomass carbon, organic gel material and a first dispersant to obtain a composite binder; mixing the composite binder, dust collecting powder and a second dispersant to obtain a mixed material containing dust collecting powder; molding the mixed material to increase the particle size of the dust collecting powder to 1mm-100mm to obtain molded particles with strength; calcining the molded particles to obtain calcined coke. Biomass carbon and organic gel material work together as binders for dust collecting powder. Biomass carbon can make the dust collecting powder have strength at room temperature, and organic gel material can make the dust collecting powder have strength after subsequent calcination; through molding, the particle size of the dust collecting powder with adhesion can be increased from the initial 75μm or less to 1mm-100mm and have strength at room temperature; the molded particles with strength can be calcined to obtain calcined coke that meets the production and use requirements of aluminum carbon anodes, achieving the goal of efficient utilization of dust collecting powder in the carbon industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0025] Figure 1 A schematic flow chart of a method for preparing calcined coke provided in an embodiment of the present application;
[0026] Figure 2 This is an appearance diagram of a calcined coke provided in an embodiment of the present application. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0028] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0029] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0031] Calcined coke is one of the main raw materials for aluminum carbon anodes. It is generally obtained by calcining petroleum coke. About 41 million tons of petroleum coke are calcined to obtain calcined coke every year in the world, of which 75% are used for the production of aluminum carbon anodes. Petroleum coke calcined dust powder refers to the powder collected by the dust collector during the calcination heat treatment process. The equipment currently used for calcining petroleum coke in my country's aluminum industry mainly includes two types: tank furnace and rotary kiln. The amount of calcined dust powder collected every year is huge. These dust powders affect the formula balance and stability of the production process, resulting in fluctuations in the volume density, strength, resistivity and other indicators of the carbon anode, and cannot enter the main production process of aluminum carbon anodes. The main treatment method is to sell them at a low price. This not only leads to an increase in the production cost of carbon enterprises, but also the dust powder is very easy to leak during the transportation and takeaway process of the enterprise, causing secondary pollution to the environment.
[0032] Therefore, the use of dust powder as raw material to prepare calcined coke in the embodiment of the present application is a solution to the problem of inefficient utilization of dust powder in the aluminum carbon industry. It can not only "turn waste into treasure" and transform the by-products produced by carbon enterprises into the main raw materials for aluminum carbon anodes, but also avoid pollution and damage to the environment during the loading and unloading and transportation of dust powder.
[0033] In a first aspect, the present application provides a method for preparing calcined coke. Figure 1 A schematic diagram of a method for preparing calcined coke provided in an embodiment of the present application; see Figure 1 , the method comprising:
[0034] S1, mixing biomass carbon, organic gel material and a first dispersant to obtain a composite binder;
[0035] In some embodiments, the mass ratio of the biomass carbon to the organic gel material is (0.01-3):1; and / or,
[0036] The mass ratio of the mixture of the biomass carbon and the organic gel material to the first dispersant is 1:(0.01-5).
[0037] Dust powder refers to the powder collected by the dust collector during the thermal treatment of petroleum coke calcination. Dust powder from petroleum coke calcination is harmful to the environment. Since dust powder particles are small, dust is easily generated. The dust powder can be one or a combination of calcined dust powder, molded dust powder, and roasted dust powder. Biomass carbon refers to a carbon-containing product formed by thermochemical conversion (such as pyrolysis) of biomass (such as organic matter such as plants and animal remains) under oxygen-deficient or oxygen-limited conditions. Biomass carbon is a solid carbonaceous material that retains most of the carbon element in biomass. Biomass carbon can be used as a binder for dust powder, and the surface of biomass carbon usually has rich functional groups, such as hydroxyl groups, carboxyl groups, etc. These functional groups can undergo physical adsorption and chemical adsorption with the surface of dust powder particles. Physical adsorption is due to the van der Waals force between molecules, which makes the dust collecting powder particles adhere to the surface of biomass carbon; chemical adsorption is through chemical bonding between functional groups, such as the acid-base reaction or complex reaction that may occur between carboxyl groups and metal oxides in dust collecting powder, thereby enhancing the bonding effect. At the same time, the porous structure of biomass carbon also helps to improve the bonding performance. Dust collecting powder particles can enter the pores of biomass carbon and be "embedded" in it to a certain extent, increasing the contact area and friction between particles, making it easier for particles to bond together. Organic gel material refers to a type of gelling material with natural or synthetic polymer compounds as the basic composition. Organic gel material has good high-temperature bonding properties and can firmly bond different materials together to form a whole, thereby meeting different needs.
[0038] Since biomass carbon and organic gel materials have different physical and chemical properties, biomass carbon can make dust collecting powder have strength at room temperature; organic gel materials can make dust collecting powder have strength after calcination; the synergistic effect of biomass carbon and organic gel materials can increase the particle size of dust collecting powder from the initial 75μm or less to 1mm~100mm and have strength at room temperature and after subsequent calcination, and finally complete the transformation from dust collecting powder to calcined coke that meets the production and use requirements of aluminum carbon anodes. Dust collecting powder cannot be used as a raw material for preparing aluminum carbon anodes because its particle size is too small. Through the composite binder, its particle size is increased from the initial 75μm or less to 20mm, and it has strength at room temperature and after subsequent calcination, and finally the dust collecting powder is "turned from waste into treasure" and can be used as a raw material for the production of aluminum carbon anodes.
[0039] The mass ratio of biomass carbon to organic gel material can be (0.01-3):1, which can ensure the best bonding ability of the composite binder, and increase the particle size of the dust collecting powder from the initial 75 μm or less to 1 mm to 100 mm and have strength at room temperature and after subsequent calcination. Exemplarily, the mass ratio of biomass carbon to organic gel material can be 0.01:1, 0.02:1, 0.03:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.5:1, 0.8:1, 1:1, 2:1, 3:1, etc. The mass ratio of the mixture of biomass carbon and organic gel material to the first dispersant is 1:(0.01-5), which can ensure the best bonding ability of the composite binder. Exemplarily, the mass ratio of the mixture of biomass carbon and organic gel material to the first dispersant can be 1:0.01, 1:0.02, 1:0.03, 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, etc.
[0040] In some embodiments, the biomass carbon includes at least one of the following: starch, sucrose, cellulose; and / or,
[0041] The organic gel material includes at least one of the following: coal tar, petroleum asphalt, and phenolic resin.
[0042] In the embodiment of the present application, the biomass carbon can be a combination of one or more of starch, sucrose, and cellulose; the organic gel material can be a combination of one or more of coal tar, petroleum asphalt, and phenolic resin.
[0043] Step S1 specifically includes: mixing the biomass carbon and the organic gel material, adding the first dispersant after stirring evenly, and stirring evenly again to obtain a composite binder. The stirring process parameters include: the stirring speed can be 10rad / min to 100rad / min; the stirring time can be 1min to 60min. Generally speaking, the first dispersant can be water.
[0044] S2, mixing the composite binder, the dust collecting powder and the second dispersant to obtain a mixed material containing the dust collecting powder;
[0045] In some embodiments, the mass ratio of the composite binder to the dust collecting powder is (0.01-1):1; and / or,
[0046] The mass ratio of the mixture of the composite binder and the dust collecting powder to the second dispersant is 1:(0.01-5).
[0047] In an embodiment of the present application, the mass ratio of the composite binder to the dust collecting powder can be (0.01-1):1, taking into account both the cost and the bonding effect. Exemplarily, the mass ratio of the composite binder to the dust collecting powder can be 0.01:1, 0.02:1, 0.03:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.5:1, 0.8:1, 1:1, etc. The mass ratio of the mixture of the composite binder and the dust collecting powder to the second dispersant can be 1:(0.01-5), which can make the second dispersant fully infiltrate and disperse the mixture of the composite binder and the dust collecting powder to improve the bonding effect. Exemplarily, the mass ratio of the mixture of the composite binder and the dust collecting powder to the second dispersant can be 1:0.01, 1:0.02, 1:0.03, 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, etc.
[0048] Step S2 specifically includes: mixing the dust collecting powder with the composite binder, stirring evenly, adding a second dispersant, and stirring evenly again to obtain a mixed material containing the dust collecting powder. The stirring process parameters include: the stirring speed can be 10rad / min to 100rad / min; the stirring time can be 1min to 60min. Generally speaking, the second dispersant can be water.
[0049] S3, molding the mixed material to increase the particle size of the dust collecting powder to 1 mm to 100 mm, and obtain molded particles with strength;
[0050] In some embodiments, the molding pressure is 1 MPa to 50 MPa.
[0051] In some embodiments, the molded particles meet the following indicators: particle size is 1 mm to 100 mm, and drop strength is ≥10%.
[0052] In the embodiment of the present application, the particle size of the dust collecting powder with adhesiveness can be increased from the initial 75μm or less to more than 20mm and has strength at room temperature through molding. The drop strength of the molded particles can be ≥10%. The drop strength is an important indicator to measure the mechanical properties of the molded particles. It indicates the proportion of particles that remain intact after falling from a certain height. Specifically, when the particles fall freely from a certain height onto a hard plane, the percentage of the unbroken mass of the particles to the original mass of the molded particles is called the drop strength. The molding pressure can be 1Mpa to 50Mpa, which can make the dust collecting powder fully molded without breaking. Exemplarily, the molding pressure can be 1Mpa, 2Mpa, 3Mpa, 4Mpa, 5Mpa, 8Mpa, 10Mpa, 15Mpa, 20Mpa, 25Mpa, 30Mpa, 35Mpa, 40Mpa, 45Mpa, 50Mpa, etc. The particle size of the formed particles can be 1mm to 100mm. The dust collecting powder is too small to be used as a raw material for preparing aluminum carbon anodes. The particle size is increased from the initial 75μm or less to 1mm to 100mm by a room temperature composite binder, and the dust collecting powder has strength at room temperature and after subsequent calcination, so that the dust collecting powder can be "turned from waste to treasure" and can be used as a raw material for the production of aluminum carbon anodes. Exemplarily, the particle size of the formed particles can be 1mm, 2mm, 3mm, 4mm, 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm, 45mm, 50mm, 55mm, 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 95mm, 100mm, etc. In addition, the pressure increase rate of the forming can be 0.1Mpa / s to 10Mpa / s.
[0053] Step S3 specifically includes: adding the mixed material into a pressure molding device, increasing the pressure to a set pressure value at a certain pressure increasing speed or directly putting it into an extrusion molding machine to obtain molded particles.
[0054] S4, calcining the formed particles to obtain calcined coke.
[0055] In some embodiments, the calcination temperature is 700°C to 1450°C.
[0056] In the embodiment of the present application, the molded particles with strength can be calcined to obtain calcined coke that meets the production and use requirements of aluminum carbon anode, so as to achieve the goal of efficient utilization of dust powder in the carbon industry from "waste to treasure". The temperature of the calcination treatment can be 700℃~1450℃, and calcined coke of aluminum carbon anode that meets the requirements can be prepared. Exemplarily, the temperature of the calcination treatment can be 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, etc. In addition, the heating rate of the calcination treatment can be 10℃ / h~100℃ / h.
[0057] Step S4 specifically includes: placing the formed particles into a high-temperature furnace such as a rotary kiln, a pot furnace, a bell furnace, etc., heating the temperature to a calcination temperature at a certain heating rate, and then maintaining the temperature for a certain time for calcination to obtain calcined coke.
[0058] In some embodiments, the calcined coke meets the following indicators: particle stability is ≥30%, resistivity is
[0059] ≤550μΩ·m, ash content is <1%.
[0060] In the examples of the present application, the calcined coke meets the following indicators: particle stability may be ≥30%, resistivity may be ≤550 μΩ·m, and ash content may be <1%, indicating that the calcined coke has excellent indicator performance. Figure 2 This is an appearance diagram of a calcined coke provided in an embodiment of the present application; see Figure 2 , indicating that the calcined coke is black and spherical.
[0061] In a second aspect, an embodiment of the present application provides a calcined coke, which is prepared by the method described in any embodiment of the first aspect.
[0062] The calcined coke is realized based on the preparation method of the calcined coke mentioned above. The specific steps of the preparation method of the calcined coke can refer to the above embodiment. Since the calcined coke adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be described one by one here.
[0063] In a third aspect, an embodiment of the present application provides a carbon anode for aluminum, wherein the raw material of the carbon anode for aluminum includes the calcined coke described in any one embodiment of the second aspect.
[0064] In the embodiments of the present application, calcined coke is prepared by using dust powder as raw material. The method has a simple process, low equipment requirements, low impurity content in the formed coke blocks, and the prepared calcined coke has excellent performance and can be directly used for the preparation of aluminum carbon anodes. It is easy to promote on a large scale, and is expected to solve the problem of efficient utilization of dust powder in the current aluminum carbon industry.
[0065] The carbon anode for aluminum is realized based on the above-mentioned calcined coke. The specific preparation method of the calcined coke can refer to the above-mentioned embodiment. Since the carbon anode for aluminum adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0066] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.
[0067] Example 1
[0068] A method for preparing calcined coke, comprising:
[0069] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0070] Specifically, 30 g of starch and 70 g of coal tar powder were stirred at room temperature for 10 min, 10 g of deionized water was added and continued to stir for 10 min to obtain a composite adhesive;
[0071] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0072] Specifically, 10 g of composite binder and 90 g of dust collecting powder were uniformly stirred for 15 min, 10 g of deionized water was added and continued to stir for 10 min to obtain a mixed material containing dust collecting powder;
[0073] The mixed material is molded to obtain molded particles with strength;
[0074] Specifically, the mixed material is added to the pressure forming equipment, the pressure is increased to 20Mpa at a rate of 0.5Mpa / s, and maintained for 30s to obtain formed particles; the formed particles meet the following requirements: particle size is 20mm; drop strength is 34%
[0075] The formed particles are calcined to obtain calcined coke.
[0076] Specifically, the formed particles are placed in a laboratory bell furnace, heated to 1250°C at a heating rate of 60°C / h, and maintained at this temperature for 2 hours before cooling to obtain calcined coke.
[0077] Example 2
[0078] A method for preparing calcined coke, comprising:
[0079] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0080] Specifically, 20 g of starch and 80 g of coal tar powder were stirred at room temperature for 10 min, and 15 g of deionized water was added and continued to stir for 10 min to obtain a composite adhesive;
[0081] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0082] Specifically, 15 g of composite binder and 85 g of dust collecting powder were uniformly stirred for 10 min, 15 g of deionized water was added and continued to be stirred for 20 min to obtain a mixed material containing dust collecting powder;
[0083] The mixed material is molded to obtain molded particles with strength;
[0084] Specifically, the mixed material is added into the pressure forming equipment, the pressure is increased to 25Mpa at a rate of 0.5Mpa / s, and maintained for 20s to obtain formed particles; the formed particles meet the following requirements: particle size is 20mm; drop strength is 37%
[0085] The formed particles are calcined to obtain calcined coke.
[0086] Specifically, the formed particles were placed in a laboratory bell furnace, heated to 1200°C at a heating rate of 40°C / h, and maintained at this temperature for 2.5 hours before cooling to obtain calcined coke.
[0087] Example 3
[0088] A method for preparing calcined coke, comprising:
[0089] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0090] Specifically, 30 g of starch and 70 g of coal tar powder were stirred at room temperature for 15 min, and 20 g of deionized water was added and continued to stir for 15 min to obtain a composite adhesive;
[0091] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0092] Specifically, 13 g of composite binder and 87 g of dust collecting powder were uniformly stirred for 10 min, 15 g of deionized water was added and continued to be stirred for 15 min to obtain a mixed material containing dust collecting powder;
[0093] The mixed material is molded to obtain molded particles with strength;
[0094] Specifically, the mixed material is added into the pressure molding equipment, and then put into the pressure molding machine. The pressure of the pressure molding machine is set to 25 MPa to obtain molded particles. The molded particles meet the following requirements: particle size is 20 mm; drop strength is 41%.
[0095] The formed particles are calcined to obtain calcined coke.
[0096] Specifically, the formed particles were placed in a laboratory bell furnace, heated to 1300°C at a heating rate of 70°C / h, and maintained at this temperature for 1 hour before cooling to obtain calcined coke.
[0097] Example 4
[0098] A method for preparing calcined coke, comprising:
[0099] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0100] Specifically, 30 g of starch and 100 g of coal tar powder were stirred at room temperature for 5 min, 5 g of deionized water was added and continued to stir for 10 min to obtain a composite adhesive;
[0101] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0102] Specifically, 25g of composite binder and 75g of dust collecting powder were uniformly stirred for 7 minutes, and 15g of deionized water was added and continued to be stirred for 7 minutes to obtain a mixed material containing dust collecting powder;
[0103] The mixed material is molded to obtain molded particles with strength;
[0104] Specifically, the mixed material is added into the pressure molding equipment, and then put into the pressure molding machine. The pressure of the pressure molding machine is set to 25 MPa to obtain molded particles. The molded particles meet the following requirements: particle size is 20 mm; drop strength is 47%.
[0105] The formed particles are calcined to obtain calcined coke.
[0106] Specifically, the formed particles were placed in a laboratory bell furnace, heated to 1250°C at a heating rate of 25°C / h, maintained at this temperature for 1h and then cooled to obtain calcined coke.
[0107] Example 5
[0108] A method for preparing calcined coke, comprising:
[0109] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0110] Specifically, 30 g of starch and 100 g of coal tar powder were stirred at room temperature for 5 min, 5 g of deionized water was added and continued to stir for 10 min to obtain a composite adhesive;
[0111] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0112] Specifically, 30g of composite binder and 70g of dust collecting powder were uniformly stirred for 10min, and 25g of deionized water was added and continued to be stirred for 7min to obtain a mixed material containing dust collecting powder;
[0113] The mixed material is molded to obtain molded particles with strength;
[0114] Specifically, the mixed material is added into the pressure molding equipment, and then put into the pressure molding machine. The pressure of the pressure molding machine is set to 25 MPa to obtain molded particles. The molded particles meet the following requirements: particle size is 20 mm; drop strength is 52%.
[0115] The formed particles are calcined to obtain calcined coke.
[0116] Specifically, the formed particles were placed in a laboratory bell furnace, heated to 1250°C at a heating rate of 25°C / h, maintained at this temperature for 1h and then cooled to obtain calcined coke.
[0117] Example 6
[0118] A method for preparing calcined coke, comprising:
[0119] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0120] Specifically, 30 g of sucrose and 70 g of phenolic resin powder were stirred at room temperature for 5 min, 5 g of deionized water was added and continued to stir for 10 min to obtain a composite adhesive;
[0121] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0122] Specifically, 30g of composite binder and 70g of dust collecting powder were uniformly stirred for 10min, and 25g of deionized water was added and continued to be stirred for 7min to obtain a mixed material containing dust collecting powder;
[0123] The mixed material is molded to obtain molded particles with strength; the molded particles meet the following requirements: particle size is 20 mm; drop strength is 58%.
[0124] Specifically, the mixed material is added into the pressure molding equipment, and then put into the pressure molding machine, the pressure of the pressure molding machine is set to 25Mpa, and the molded particles are obtained;
[0125] The formed particles are calcined to obtain calcined coke.
[0126] Specifically, the formed particles were placed in a laboratory bell furnace, heated to 1250°C at a heating rate of 25°C / h, maintained at this temperature for 1h and then cooled to obtain calcined coke.
[0127] Comparative Example 1
[0128] A method for preparing calcined coke, comprising:
[0129] Mixing the dust collecting powder and the second dispersant to obtain a mixed material containing the dust collecting powder;
[0130] Specifically, 100 g of dust collecting powder was taken and stirred evenly for 10 min, 25 g of deionized water was added and continued to stir for 7 min to obtain a mixed material containing dust collecting powder;
[0131] The mixed material is molded to obtain molded particles with strength;
[0132] Specifically, the mixed material is added into the pressure molding equipment, and then put into the pressure molding machine. The pressure of the pressure molding machine is set to 25 MPa to obtain molded particles. The molded particles meet the following requirements: particle size is 20 mm; drop strength is 4%.
[0133] The formed particles are calcined to obtain calcined coke.
[0134] Specifically, the formed particles were placed in a laboratory bell furnace, heated to 1250°C at a heating rate of 25°C / h, maintained at this temperature for 1h and then cooled to obtain calcined coke.
[0135] Comparative Example 2
[0136] A method for preparing calcined coke, comprising:
[0137] Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder;
[0138] Specifically, 30 g of starch and 100 g of coal tar powder were stirred at room temperature for 5 min, 5 g of deionized water was added and continued to stir for 10 min to obtain a composite adhesive;
[0139] The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder;
[0140] Specifically, 30g of composite binder and 70g of dust collecting powder were uniformly stirred for 10min, and 25g of deionized water was added and continued to be stirred for 7min to obtain a mixed material containing dust collecting powder;
[0141] The mixed material is molded to obtain molded particles with strength;
[0142] Specifically, the mixed material is added into the pressure molding equipment, and then put into the pressure molding machine. The pressure of the pressure molding machine is set to 25 MPa to obtain molded particles. The molded particles meet the following requirements: particle size is 20 mm; drop strength is 51%.
[0143] The formed particles are calcined to obtain calcined coke.
[0144] Specifically, the formed particles were placed in a laboratory bell furnace, heated to 500°C at a heating rate of 25°C / h, maintained at this temperature for 1 hour and then cooled to obtain calcined coke.
[0145] The calcined coke prepared in the above-mentioned embodiments was tested in accordance with relevant industry standards. The test results are shown in Table 1.
[0146] Table 1 Test of relevant physical and chemical indicators of calcined coke
[0147] Serial number Particle stability (%) Drop strength (%) Resistivity (μΩ·m) Ash content (%) Example 1 51 34 481 0.39 Example 2 56 37 487 0.41 Example 3 59 41 493 0.37 Example 4 68 47 486 0.43 Example 5 75 52 486 0.36 Example 6 71 58 494 0.56 Comparative Example 1 11 4 497 0.38 Comparative Example 2 26 51 984 0.41
[0148] As can be seen from Table 1, the calcined coke obtained by the preparation method of calcined coke provided in the embodiment of the present application has high particle stability, high drop strength, low powder resistivity and low ash content, which meets the raw material requirements of aluminum carbon anodes and can be directly put into the main process of aluminum carbon anode production. The preparation method is simple, low cost, and very easy to industrialize and mass produce. However, no composite binder is used in Comparative Example 1, and the calcination temperature in Comparative Example 2 is low, which to a certain extent leads to poor performance of the calcined coke prepared in Comparative Examples 1-2, which cannot meet the raw material requirements of aluminum carbon anodes.
[0149] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:
[0150] (1) In the present embodiment, a composite binder is first prepared, and then the composite binder, dust collecting powder and deionized water are mixed to make the dust collecting powder have a certain adhesiveness. The particle size of the dust collecting powder with adhesiveness is increased from the initial 75 μm or less to 1 mm to 100 mm and has a certain strength at room temperature by pressure forming. Finally, calcined coke that meets the production and use requirements of aluminum carbon anodes is obtained by calcination, thereby achieving the goal of "turning waste into treasure" and efficiently utilizing dust collecting powder in the carbon industry;
[0151] (2) The calcined coke provided in the embodiments of the present application meets the following indicators: particle stability can be ≥30%, resistivity can be ≤550 μΩ·m, and ash content can be <1%;
[0152] (3) The calcined coke prepared by using dust powder as raw material in the embodiment of the present application has a simple process, low requirements on equipment, low impurity content in the formed coke blocks, and the prepared calcined coke has excellent performance and can be directly introduced into the main process of preparing aluminum carbon anodes. It is easy to promote on a large scale and is expected to solve the problem that dust powder cannot be efficiently utilized in the current aluminum carbon industry.
[0153] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing calcined coke, the method comprising: Mixing the biomass carbon, the organic gel material and the first dispersant to obtain a composite binder; The composite binder, the dust collecting powder and the second dispersant are mixed to obtain a mixed material containing the dust collecting powder; Molding the mixed material to increase the particle size of the dust collecting powder to 1 mm to 100 mm, thereby obtaining molded particles with strength; The shaped particles are calcined to obtain calcined coke.
2. The method according to claim 1, characterized in that The mass ratio of the biomass carbon to the organic gel material is (0.01-3):1; and / or, The mass ratio of the mixture of the biomass carbon and the organic gel material to the first dispersant is 1:(0.01-5).
3. The method according to claim 1 or 2, characterized in that: The biomass carbon includes at least one of the following: starch, sucrose, cellulose; and / or, The organic gel material includes at least one of the following: coal tar, petroleum asphalt, and phenolic resin.
4. The method according to claim 1, characterized in that The mass ratio of the composite binder to the dust collecting powder is (0.01-1):1; and / or, The mass ratio of the mixture of the composite binder and the dust collecting powder to the second dispersant is 1:(0.01-5).
5. The method according to claim 1, characterized in that The molding pressure is 1Mpa to 50Mpa.
6. The method according to claim 1 or 5, characterized in that: The molded particles meet the following indicators: particle size is 1 mm to 100 mm, and drop strength is ≥10%.
7. The method according to claim 1, characterized in that The calcination temperature is 700°C to 1450°C.
8. The method according to claim 1, characterized in that The calcined coke meets the following indicators: particle stability is ≥30%, resistivity is ≤550 μΩ·m, and ash content is <1%.
9. A calcined coke, wherein the calcined coke is prepared by the method according to any one of claims 1 to 8.
10. A carbon anode for aluminum, wherein the raw material of the carbon anode for aluminum comprises the calcined coke according to claim 9.